Logistics management model for the company tramacco express Riobamba - Moreno Ayala, Jessica; Villacis Betancourt, Cristhian Andrés; Martínez Nogales, Juan Manuel; Lara Sinaluisa, Jorge Milton (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June)DO - 10.36779/mktdescubre.v1i21.806, 2023)
The proposal of a logistics management model for the company Tramaco Express located in the city of Riobamba aims to design a logistics management model to improve the distribution process of the company. A diagnosis of it was made, through a qualitative-quantitative approach, the instruments and techniques used were surveys and interviews. It was possible to know the problems that the company has, being one of the main ones the delay in delivery times, information was also collected about the personnel that works in the company to know their functions. With the data collected and once the processes were characterized, the proposal was prepared based on the development of a 5-stage model, consisting of flow charts and check lists for the different processes that the company has. This seeks to improve and optimize management. The model contributes to improving the logistics processes of the company, allowing all activities to be carried out in the best way and in an efficient and effective way, thus fulfilling all the objectives set.